Desvelando sentidos de práticas educativas de famílias de classes populares: um estudo realizado com famílias de baixa renda de um bairro no município de São Paulo - Cruz, Shirley Pires (2008)
The following study tried to reveal and comprehend educational practicals in families that live in a lower class neighborhood in Sao Paulo city. Revealing the senses of educational practicals of these families, it has been, firstly, entering their worlds, contextualize their living experiences, and in order to do that, it has been important and revealing get to know their particulars, because the intention of this research has not been only to generalize the senses of the familiar educational practicals. The sense can be comprehended in this work, like the path where these practicals point, it means, the direction of the configured practicals from the narrative obtained from the interviewed families. It s important to remember that, the sense appear according to the situation, which means, within space and time, within a determined context or season, therefore what has emerged from this research refers to investigation that has taken place. This is an existential qualitative phenomenological research. As part of this study we have two families from EMEF s students of the neighborhood. These two families have taken two meetings where reflexive interviews were made, according to Szymanki proposal, besides the testimonies taken in group meetings. The data analysis was inspired on the Existential Phenomenology that was applied to get the educational practicals from their speeches. The results achieved point that the educational practicals of the studied families reveal the sense of being a father and a mother and take the role of being the educators of their own children, leading them to a better life. We haven t noticed a dialogic practical, but a command respect-obedience relationship, although this image of a educator family, committed in their children education, most of the times do not adequate to the concept that some educators have about lower-class families